Pemanfaatan Limbah Beton K 250 Sebagai Substitusi Agregat Kasar Pada Campuran Laston Lapis Antara (AC-BC) - Ananda, Rizki Fajri; Shalahuddin, Muhammad; Yusa, Muhamad (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Pavement construction requires aggregate which is non renewable material. Concrete waste such as from cubic test might be recyded. This study investigated marshall characteristic of Asphalt concretebinder course (AC-BC) which used of concrete waste as coarse aggregate substitute. Concrete waste was mixed with fresh aggregate at ratio of 100:0, 75:25, 50:50, 25:75 and 0:100 Asphalt contentvariation are 5%, 5.5%, 6%, 6.5% and 7%. The optimum aggregate contents for each variation are 6.08%, 5.83%, 5.87%, 5.10%, 5.55% respectively. The result show that all variation fulfilled the specification The 75:25 variation is recommended as mixture ratio with high stability value of 1445 Kg, Flow 3.40 mm, VMA 15.30%, VFA 77.50%, VIM 3.40%, MQ 440 Kg/mm and also asphalt content is affordable with 5.87% of optimum asphalt content.Keywords: AC-BC, Concrete Waste, Coarse Agregate